PENGEMBANGAN TAS SELEMPANG DENGAN LIMBAH MATERIAL POLIPROPILENA DI UKM KAMPOENG RADJOET - Amirullah, Burhan Fajar; Sadika, Fajar; Muchlis, Muchlis (Telkom University, 2024)
Small and medium enterprises have a very important role in the economic cycle in the community. Especially in creating jobs and a source of income for the middle to lower economic community. Kampoeng Radjoet is a knitting industry in Bandung. Kampoeng Radjoet produces a wide range of products ranging from sweaters, cardigans, vests, etc. However, the large-scale production produced by Kampoeng Radjoet also has a negative impact on the industry itself. Namely with the emergence of various knitting wastes from fabrics to knitting yarns. Therefore, Kampoeng Radjoet wants to utilize this knitting waste to become a new wearable product from the existing waste. Through an observational approach, this research aims to understand the phenomenon of waste knitting fabric pieces from leftover production by conducting a field survey at Kampoeng Radjoet. In addition, with the MFC (Morphological Force Connection) method and polypropylene product waste materials, various new products can be developed that are worth selling for Kampoeng Radjoet while reducing the impact of knitting waste. Keywords: Kampoeng Radjoet, knitting waste, MFC , polypropylene.